2021
DOI: 10.1029/2021gl096181
|View full text |Cite
|
Sign up to set email alerts
|

Blended Dry and Hot Events Index for Monitoring Dry‐Hot Events Over Global Land Areas

Abstract: The amplifying effects of disasters caused by compound dry and hot extremes (dry‐hot events) have attracted widespread attention. This study presents a novel Blended Dry and Hot Events Index (BDHI) considering various dry and hot conditions (i.e., dry/hot, dry/cool, wet/hot, and wet/cool conditions). BDHI was applied to monitor dry‐hot events over global land areas during the 1950–2019 period and its performance was compared against that of the Standardized Compound Event Indicator (SCEI), which includes certa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 38 publications
(80 reference statements)
0
29
0
Order By: Relevance
“…According to these classifications, CDHEs belong to multivariate compound events, driven by high‐temperature anomalies combined with severe precipitation deficit. It was found that climate change enhanced the frequencies, severities, and other characteristics of CDHEs over many regions worldwide (Wu, Su, & Singh, 2021). For instance, Europe was invaded by extreme heatwaves and severe precipitation deficit in 2003, 2010, and 2018, leading to massive losses of crops, wildfires, and increased human mortality and morbidity (Bastos et al., 2014; Ribeiro et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to these classifications, CDHEs belong to multivariate compound events, driven by high‐temperature anomalies combined with severe precipitation deficit. It was found that climate change enhanced the frequencies, severities, and other characteristics of CDHEs over many regions worldwide (Wu, Su, & Singh, 2021). For instance, Europe was invaded by extreme heatwaves and severe precipitation deficit in 2003, 2010, and 2018, leading to massive losses of crops, wildfires, and increased human mortality and morbidity (Bastos et al., 2014; Ribeiro et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding drought prediction at a short temporal scale (e.g., semimonthly), especially during severe compound dry‐hot conditions (Bevacqua et al., 2022; Wu, Su, & Singh, 2021), is of critical importance for the practitioners and stakeholders for taking powerful measures in advance to reduce more potential impactful water shortage (Wu, Su, Singh, et al., 2021). Finally, robust drought prediction on the basis of this work can provide valuable information for water‐use sectors at an early stage, and therefore the sectors can take appropriate measures to cope with associated drought risks.…”
Section: Discussionmentioning
confidence: 99%
“…Drought, as a widespread natural hazard in any climate regime, has disastrous impacts on agricultural activity, water resources management, and human health, resulting in crop failure, ecosystem degradation, and political conflicts, with wide‐ranging socioeconomic effects (Ault et al., 2016; Jiang et al., 2022; Stevenson et al., 2022; Williams et al., 2020; Wu, Su, & Singh, 2021). Mounting severe drought events, for example, the 2014 North China drought (Wu, Su, Singh, et al., 2021), the May 2017 flash drought in the U.S. Northern Plains (Xu et al., 2020; Zarekarizi et al., 2021), the 2021 Canada and the USA drought (Schiermeier, 2021), and the long lasting 2000–2021 southwestern North American megadrought (Williams et al., 2020, 2022), have occurred in recent decades, contributing to large economic, food, water, and ecosystem insecurity (Coffel et al., 2019; Hameed et al., 2020; Xu et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further analyze the contributions of the temperature and precipitation changes to the trend of the dry spell duration, a multiple linear regression method (Wu et al, 2021) was applied. First, multiple linear regression was adopted to calculate the duration predicted and regressed by the temperature and precipitation on each grid:…”
Section: Relative Contribution Analysismentioning
confidence: 99%